2021
DOI: 10.3389/fphar.2021.639095
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic RGD Pentapeptide Cilengitide Enhances Efficacy of Gefitinib on TGF-β1-Induced Epithelial-to-Mesenchymal Transition and Invasion in Human Non-Small Cell Lung Cancer Cells

Abstract: During non-small cell lung cancer (NSCLC) progression, transforming growth factor (TGF)-β mediated epithelial-to-mesenchymal transition (EMT) is an important process leading to high mortality and poor prognosis. The EMT is a fundamental process for morphogenesis characterized by the transformation of cancer cells into invasive forms that can be transferred to other organs during human lung cancer progression. Gefitinib, an epidermal growth factor receptor (EGFR) inhibitor, has shown anti-proliferative effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
4
9
0
Order By: Relevance
“…In a previous report on cilengitide combined with the EGFR inhibitor gefitinib, we confirmed their cytotoxicity in CPAE cells and a synergistic effect on NSCLC cell viability and TGF-β1–induced EMT phenotype changes [ 36 ]. Based on that study, we investigated the combined treatment effect of cilengitide with erlotinib on NSCLC cell viability and TGF-β1–induced EMT marker expression.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…In a previous report on cilengitide combined with the EGFR inhibitor gefitinib, we confirmed their cytotoxicity in CPAE cells and a synergistic effect on NSCLC cell viability and TGF-β1–induced EMT phenotype changes [ 36 ]. Based on that study, we investigated the combined treatment effect of cilengitide with erlotinib on NSCLC cell viability and TGF-β1–induced EMT marker expression.…”
Section: Resultssupporting
confidence: 75%
“…We also tested the effect of cilengitide with erlotinib on TGF-β1–induced invasion in A549 cells. In our previous report, we confirmed that cilengitide has an inhibitory effect and that combined treatment with gefitinib yielded a synergistic effect [ 36 ]. As shown in Figure 6 A, either erlotinib or cilengitide inhibited the TGF-β1–induced invasion of A549 cells across the gelatin-coated membrane, and their combination increased this inhibitory effect.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Cilengitide is supposed to enhance the inhibition of erlotinib on TGF-β1-induced EMT and phosphorylation of SMAD2/3 [304,305]. In a phase I study, continuous infusion of cilengitide plus chemoradiotherapy for patients with stage III non-small cell lung cancer is potentially tolerable.…”
Section: Cilengitidementioning
confidence: 99%